Immigrant networks, information transmission and labor market outcomes - Barbosa, Samuel de Souza (2019)
This paper attempts to replicate, using Brazilian census data, results on immigrant assimilation in labor market of host countries, supported by a known model of job information transmission through social networks. It discusses how the model connects social networks and job market outcomes, and how its predictions may reveal in the data. Empirical estimates suggests that immigrant networks in metropolitan areas finds jobs for their members, but there is no evidence supporting that it channels them into higher-wage or main occupations, even though descriptive data indicates specialization patterns amongst immigrants.